Penerapan Penggunaan Aplikasi Tesaurus dan Vlognow terhadap Keterampilan Menulis Teks Puisi pada Siswa Kelas VIII SMPN 13 Gorontalo Tahun Pelajaran 2023/2024: Penelitian - Ibrahim H. Dukalang; Sitti Rachmi Masie; Eka Sartika (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The objectives of this study are to: (1) describe the use of the Thesaurus and VlogNow applications as media tools for enhancing poetry writing skills, and (2) describe students' ability in utilizing the Thesaurus and VlogNow applications in writing poetry texts. This study employs a qualitative descriptive approach. The data collection techniques used include observation, interviews, tests, and documentation. The data in this study consist of students’ poetry texts and poetry videos created through the application of the Thesaurus and VlogNow media tools. The results of the study indicate that the use of the Thesaurus and VlogNow applications has a positive impact on improving students' poetry writing skills. Students became more active and motivated in participating in poetry writing lessons. This is evident from the increase in the average score achieved by students after using the Thesaurus and VlogNow applications, which reached 87.36. This score is significantly higher than the average score before using the Thesaurus application, which was 51.79. This success demonstrates that innovations in teaching methods can have a significantly positive effect, especially in Indonesian language subjects, which are often perceived as difficult by some students